Analisis Kinerja UPT Perparkiran Dalam Pengelolaan Parkir Di Kabupaten Kudus - Muhammad Arie Munandar; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The Parking Technical Unit (PTU) of Kudus Regency is an organization to handle parking in Kudus Regency, Central Java. Good parking management must be applied to achieve organizational goals, therefore organizational performance can be maximized. This study aims to analyze the organizational performance of Kudus PTU, as well as supporting faktors and performance barriers of the PTU in the parking management of Kudus Regency. Type of research is descriptive with qualitative approach, conducted at the PTU of Kudus Regency. Data collection techniques were interviews, observation and documentation. The results showed that the performance of Kudus PTU Parking in parking management was still not optimal because the four indicators, namely productivity, responsiveness, responsibility and accountability, were not in a good condition yet. Productivity of parking revenues has not reached the specified target. The responsiveness aspect has not been maximized because the programs aimed at by the community have not been evenly distributed such as the installation of a portal machine in the parking area only installed a few places and not all parking uniforms have a complaint number. Then the responsibility aspects are still not maximal because of the parking rates are not in accordance with the existing regulations. Accountability carried out by the PTU is only internal, since parking revenues was not publicly reported. Supporting faktors of performance at the UPT Parking are leadership and its inhibiting faktors, personal faktors, team faktors, faktor systems and human resource faktors